Subdiaphragmatic bronchogenic cysts: Case series and literature review - Xiao, Jianchun; Zhang, Xueyang; Zhou, Hongru; Hong, Tao; Li, Binglu; He, Xiaodong; Liu, Wei (Frontiers in Medicine, 2022)
Bronchogenic cysts are congenital malformations caused by aberrant foregut budding. They major occur in the thorax, with subdiaphragmatic cases being uncommon. Here, we present a series of 19 patients diagnosed with subdiaphragmatic bronchogenic cysts histopathologically at a single institution in China from 2012 to 2021. A literature review was also conducted by searching the PubMed database using keywords related to “bronchogenic cysts” and “subdiaphragmatic,” yielding 107 cases. Taken together, the 126 cases had a median age of 41.0 years (interquartile range, 30.0–51.0 years) and 62 of them were male (49.2%). The cysts were most commonly detected in the left adrenal region (36.2%), followed by the pancreatic region (11.5%) and gastric cardia/lesser curvature of the stomach (9.2%). All patients except two underwent surgery for a definite diagnosis, symptom alleviation, and (or) malignancy prevention. Most patients recovered fast and were discharged from the hospital within 1 week after surgery, and the surgical complications were infrequent. The prognosis was generally favorable, as no recurrence was reported during the follow-up as long as 77 months.